Management of Services for Prospective Hajj Pilgrimages Post COVID-19 Office of the Ministry of Religion Rejang Lebong District - Syaiful Bahri; Murni Yanto; Tanimu Adam Ibrahim (CV Media Inti Teknologi, 2025)
This research aims to reveal how services were provided to prospective pilgrims, particularly in 2022, after a two-year Hajj suspension due to the COVID-19 outbreak. The study focuses on the Office of the Ministry of Religious Affairs of Rejang Lebong Regency. Employing a descriptive approach, the research subjects included the Head of the Office, the Head of the Hajj and Umrah Organizer, staff, and prospective pilgrims. Data was gathered through observation, interviews, and documentation, and analyzed through data collection, presentation, and conclusion drawing. Triangulation was used for data validity. The findings indicate that the management of Hajj services post-COVID-19 in Rejang Lebong, encompassing planning, organizing, implementation, and supervision, maintained pre-pandemic service principles, especially regulatory guidelines. However, differences emerged in the overall climate, atmosphere, and pilgrim numbers, with only 50% of the regular quota (282 pilgrims) being allocated, and an age limit under 65 years imposed. This research is novel, as there has been a lack of studies on post-COVID-19 Hajj services. In conclusion, the post-COVID-19 Hajj services in Rejang Lebong effectively adapted to health protocols and limited quotas while upholding pre-pandemic service principles. Despite changes in the atmosphere and pilgrim numbers, the Office of the Ministry of Religious Affairs successfully delivered services through structured and adaptive management.